Challenges and Opportunities of Regional Autonomy in Indonesia: A Case Study of Provincial Expansion in Papua - Dhanu Rizky Wahyurinata; Devan Ganicia Syah P; M Asif Nur Fauzi (SWATANTRA, 2026)
This study aims to explore the implementation of regional autonomy and decentralization in Indonesia and its impact on regional economic development. Regional autonomy, introduced in 2001, is intended to grant greater authority to local governments in governing and managing their territories. Decentralization is expected to enhance governance efficiency and the welfare of local communities. However, the implementation of these policies faces various challenges, including disparities in access to economic resources and low civil society participation in policy-making. A case study on the provincial expansion in Papua reveals the complexities in implementing regional autonomy, such as financial readiness, infrastructure, and resistance from some local communities. In conclusion, while regional autonomy and decentralization can bring significant benefits to local development, further efforts are needed to address existing challenges to ensure that these policies can be effectively implemented and positively impact communities.